Prediction of Shear Strength for Steel-Fiber High-Strength Concrete Corbels with the Softened Strut-and-Tie Model - Shu-Shan Li; Jin-Yan Zheng; Feng-Jian Zhang; Hong-Mei Li; Ming-Xiao Jia; Zu-Jun Liu; Ai-Jiu Chen; Wei Xie (Buildings, 2023)
On the basis of the test results of nine steel-fiber high-strength concrete corbel specimens subjected to a vertical load, the influence of the steel fiber content on the shear performance of corbels was analyzed. The softened strut-and-tie model (SSTM) was used to analyze the shear strength of steel-fiber high-strength concrete corbels, taking into consideration the shear contribution of steel fibers. A calculation model for the shear strength of steel-fiber high-strength concrete corbels is proposed, and a database for 26 steel-fiber high-strength concrete corbels was created by using the model. The results obtained according to the codes ACI318-19, EC2, CSA A23.3-19 and the softened strut-and-tie model were compared with the experimental values to verify the rationality of the model. The findings showed that steel fiber can effectively limit the crack width and improve the crack morphology. The overall average value of the ratio between the experimental and the predicted strengths of the model was 1.082, and the variance was 0.004. The values predicted with the proposed calculation model were closer to the experimental values than those calculated according to the codes. This study provides a definite mechanical model that can reveal the shear mechanism of steel-fiber high-strength concrete. It can reasonably predict the shear strength of steel-fiber high-strength concrete corbels.